An electrical power control system for explorer-class remotely operated underwater vehicle (ROV) - Muhammad Ikhsan Sani; Simon Siregar; Muhammad Muchlis Kurnia; Dzikri Hasbialloh (Universitas Ahmad Dahlan, 2019)
The importance of an optimal method for electric power transmission is crucial for ROV operation. Meanwhile, only few studies have shown the effect of electrical power system from power supply to ROV.This paper proposes a design and implementation of electrical power system for ROV that developed by Tech_SAS team from Telkom University, Bandung, Indonesia. This work aims to obtain the optimal power system to supply ROV’s electrical and electronic components. Tech_SAS ROV is developed to compete on 1st and 2nd ASEAN MATE Underwater Robotic Competition. The system has demonstrated that 48V electric voltage can be transmitted to ROV with negligible voltage drop when using 20 meter 12AWG cable. The voltage is converted to 12V using DC-DC converter in order to supply various ROV’s electronic devices ROV safely and efficiently. Meanwhile, the microcontroller was used to as thrust control to manage current flow to DC motor. The system has been evaluated and demonstrates optimal results and provides a design consideration about ROV’s power system especially on tether cable and power distribution scheme.